Reclaiming the voices and spaces for the youth of Vilakazi Street: Exploring spatial reform in Orlando West - Dakile, Sinqobile (Faculty of Engineering and the Built Environment, 2023)
The legacy of apartheid spatial planning is still evident under South Africa's democratic government. Townships are segregated dormitories with residents who still face many inequities in their daily lives. Soweto is a township which a deep history of struggle for liberation. Vilakazi street is especially symbolic due to all the activists who used their voices as a tool to fight against a system of inequality. Today Soweto is in a transitional phase. It has developed from what was once a dormitory township to a diverse, resilient community of people who have reclaimed the spaces as their own. This research serves to gain a deeper understanding of Vilakazi Street (as a catalyst to transformation) - an emerging high street in a culturally rich neighbourhood of Orlando West. Furthermore to understand the missing links and gaps which can better improve the quality of life for the community. It is also important to gain a deeper understanding of the legislation and contributing factors that enable the development of the existing vibrant township culture. Furthermore to learn what role the youth of today contribute to. Orlando West The research is guided and grounded in a theoretical framework which highlights the importance of democratic planning processes and enabling resident's voices in the design processes. The methodology and methods speak on the approach to gain research on the ground and the interactions with the local residents and their everyday spaces. A contextual analysis is done on the metro scale to better understand the role of Orlando West in relation to the city and a neighbourhood scale analysis is done to better understand the role Vilakazi Street plays in it's neighbourhood. This is followed by a case study which is used as a precedent to address and create inclusive design for the youth of Soweto. The proposal aims to improve and amplifying the vulnerable voices of the youth.